(untitled) (Bangladesh Journal of Zoology, 2022)
This paper was aimed to focus on the situation and the source of short-lived climate pollutants (SLCPs) in the atmosphere of Bangladesh and their impact on the environment and health. The study used a qualitative research methodology and a review of the relevant literature to fulfill the objectives. The study showed that SLCPs were the most important air pollutants and responsible for reducing crop yields. These also had significant adverse impacts on health, agriculture and climate. The black carbon (BC) and the ozone caused adverse health impacts, which are likely leading to premature deaths in Bangladesh. The SLCPs may have direct adverse impacts on the economy, health, agriculture production, ecosystems, biodiversity, and climate change. Strategic measures should be undertaken to reduce and mitigate the SLCPs in the atmosphere of Bangladesh. Therefore, several necessary steps including introducing clean-burning biomass stoves for cooking, encouraging diesel to CNG conversion vehicles, replacing traditional brick kilns with modern technologies, and stopping the burning of agricultural residue are recommended. Bangladesh J. Zool. 50 (1): 3-21, 2022